PREVALENCE OF HELICOBACTER PYLORI AMONG ASYMPTOMATIC POPULATIONS IN SANA’A, YEMEN - Alyahawi, Ali; Alkaf, Ali; Alzaghrori, Samar (Universal Journal of Pharmaceutical Research, 2018)
Objective: Helicobacter pylori consider the most important cause of chronic gastritis and also the most important etiological factor responsible for the duodenal and gastric ulcer and have an important role in the pathogenesis of gastric cancer. The aim of the present study to know the prevalence of H. pylori among the khat chewing adults in compared to non-khat chewing among asymptomatic populations. Methods: A total of 82 healthy subjects were screened to find out the prevalence of Helicobacter pylori using stool antigen card test during the period started in 16 April 2018 and ending in 8 May 2018 in Sana’a, Yemen. Predesigned questionnaire was used to collect information such as age, sex, education status, khat chewing, smoking, tobacco chewing, occupation, and tests results all above data were recorded for each subject. Results: Patients who had taken proton pump inhibitors or antibiotic for a month prior to study were excluded. Out of these 82 asymptomatic individuals, 36 were found positive for Helicobacter pylori by the test, giving a prevalence of 43.9%. A prevalence of 26.9% (62.9% of khat chewing) was khat chewing individuals and it had statistically significant difference. A prevalence of 14.6% was seen among cigarette smoking participants. Conclusion: The present study revealed substantial prevalence of Helicobacter pylori in khat chewing healthy subjects. A higher prevalence of Helicobacter pylori seen in these subjects may be contributed to khat chewing. Identification of khat chewing populations, who do not show symptoms of Helicobacter pylori infection, is essential for controlling the infection and it still remains a challenge for the clinicians. Peer Review History: Received 25 March 2018; Revised 11 May; Accepted 12 June; Available online 15 July 2018 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewer(s) detail: Dr. Rashad Mohammed Musleh Alnamer , University of Thamar, Yemen, yemtiger1@yahoo.com Dr. Razan Hani Amin Haddad , Jordan University of Science and Technology, Jordan, razanhh@yahoo.com